Analysis of European Discourses on Adult Education and Training and Lifelong Learning - Manuela Terrasêca; João Caramelo; Teresa Medina (Universidad de Granada, 2011)
In the most recent years, the European Union published a set of documents with diverse statutes that have been setting the agenda of the so-called "European dimension of education", in particular concerning to education, training and lifelong learning. Several analyses are being produced on these European discourses with emphasis on the criticism about: i) its political pragmatism (Canário, R., 2003), ii) its vocational bias, iii) the transformation of State, Work and Citizenship relations induced by these European texts (Lima, L., 2003, Medina, T., 2002). In this article the authors intend to identify and to characterize the "profiles" of Citizen, State and Labor that emerge from the European discourses. The aim is to highlight how these discourses produce and induce a legitimate framework and meaning for the field and policies on adult education.